The simulation of urban growth applying sleuth ca model to the yilan delta in Taiwan - Yea, Chung Ding; Yong, Kui Zhang (2007)
The SLEUTH model developed by Clarke, based on the Cellular Automata (CA) city expansion development theory, can be applied to city development simulation in metropolitan areas. If we want to predict urban development trends, many microcosmic changes of parameter can cause major changes in the predicted result due to the complexity and indefinite nature of parameters. The SLEUTH model has been applied to the Silicon Valley of San Francisco and in Washington D.C. In fact, there have been good results applying this method in other countries such as Australia, Vietnam, Egypt and Portugal. In this study we explore the simulation of urban growth applying SLEUTH model to three cities: Yilan, Luodong and Suao in the Yilan Delta area of northeast Taiwan to study the dynamics of the region using historical data. After carrying out the SLEUTH prediction method, we found that the result of its application for predicting city development in the Yilan Delta area shows that the cities of Yilan and Luodong are developing and expanding more evenly from the city center, partly because of their large dockland areas, while Suao city has expanded only along the main road, due to the limit of the steep mountain slope inland. However, if one wants to improve the dependability of the prediction, one must consider the influence of fast changes in urban social systems in Taiwan.